The Effect of Using Anagram Games of Students’ English Vocabulary Mastery - Ade Imas Nurwulandari; Asnawi (Indonesian Journal of ELT and Applied Linguistics, 2022)
The objective of this research was to find out the effect of using anagram game of students’ english vocabulary mastery at the eighth-grades of SMP Negeri 2 Deli Tua Academic Year 2021/2022. The type of research was quantitative research, and it was conducted by using experimental design with two classes, in experimental class consisted of 30 students and control class consisted of 30 students. In technique of collecting data, the researcher conducted pre-test, treatment and post-test by vocabulary test. The data were analyzed by using t-test formula. The result of the data showed that tobserve (11,2) value was higher than the ttable in which tobserve>ttable (11,2>1,68). The finding showed that the hypothesis was accepted. It can be concluded that there was significant difference score in vocabulary skill for the students who were taught by anagram media and who were not taught by anagram media. Based on the explanation above, the researcher concluded that Anagram Media is effective for teaching students’ understanding in learning vocabulary skill of the eighth-grade students at SMP Negeri 2 Deli Tua Academic Year 2021/2022